Scaling-up of Agriculture Water Management Interventions for Building System Resilience in Bundelkhand Region of Central India - CGIAR Research Program on Water, Land and Ecosystems (2021)
Case study on Agricultural water management interventions was prepared for FAO-SOFA report 2021.